Long-term efficacy of proton pump inhibitors as a treatment modality for eosinophilic esophagitis. Issue 9 (September 2022) - Thakkar, Kisan P.; Fowler, Mark; Keene, Staci; Iuga, Alina; Dellon, Evan S.
Abstract: Background: Proton pump inhibitors (PPIs) are a first-line treatment for EoE, but data are limited concerning response durability. We aimed to determine long-term outcomes in EoE patients responsive to PPI-therapy. Methods: We conducted a retrospective cohort study of newly diagnosed adults with EoE who had initial histologic response (<15 eosinophils per high-power-field) to PPI-only therapy. We extracted data regarding their subsequent clinical course and outcomes. We compared findings between the initial PPI-response endoscopy and the final endoscopy, and assessed factors associated with loss of PPI response. Results: Of 138 EoE patients with initial histologic response to PPI, 50 had long-term endoscopic follow-up, 40 had clinical follow-up, 10 changed treatments, and 38 had no long-term follow-up. Of those with endoscopic follow-up, mean follow-up-time was 3.6 ± 2.9 years; 30 and 32 patients (60%; 64%) maintained histologic and symptom responses, respectively. However, fibrotic endoscopic findings of EoE were unchanged. Younger age (aOR 1.05, 95% CI: 1.01–1.11) and dilation prior to PPI treatment (aOR 0.21, 95% CI: 0.05–0.83) were the only factors associated with long-term loss of PPI response. Conclusions: Long-term histologic and clinical response rates for PPI therapy were 60% and 64%, respectively. Younger age and dilation at baseline were associated with histologic loss of response. These data can inform long-term EoE treatment selection.